The evidence for the influence of musical compositions during pregnancy to the structure and functions of the offsprings’ brain - Hermanto Tri Joewono (Universitas Airlangga, 2020)
Objective: to compile studies in Surabaya on the effect of Mozart compositions during pregnancy on the number of the offsprings brain neuron, glia, BDNF, apoptotic neurons and, neuronal dendritic density. These series of studies aimed to develop environmental-enrichment model during pregnancy so we can have better brain for the next generation. Better brain means better capacity in processing information, solving the problems, and creating new solutions that depends on the number of neuron, glia, ratio glia/ neuron and synapses. We do believe in the motto of “From Neurons to Nation” Overview: There were 38 studies, in animal models except two in human subjects, all of them with control, prospective, and randomized. The first group consist of analyze the frequency, sequence, time, duration, gestational age, distant, and intensity of Mozart composition. The second group: try to analyze the mechanism and compare with variety of other compositions including other western music(Chopin, Beethoven, Blues, Jazz, Rock) and Indonesian music(Gamelan Jawa, Sunda, Bali, Pop, Religious). The third group: combine with nutrition, reverse sequence, involving cerebrum and cerebellum, and right-left hemisphere. There were no growth restricted, dead, and malformed offsprings in both groups. The BDNF expression, synapsin I expression, the number of neuron, number of glia, and dendritic density of the exposed groups were higher than control. The neuronal apoptotic index were lower in the exposed groupsConclusions: Mozart compositions during pregnancy increased the BDNF, synapsin I, number of neuron, number of glia, dendritic density and, also decreased the neuronal apoptosis in offsprings’ brain